Microfacies and depositional environment of theAsmari Formation of the Bandar-pol anticline, Zagros Basin, South of Iran - Hashmie, A.; Najafie, A.; Rezaei, P.; Ghorbanie, M. (Sulaimani Journal for Pure and Applied Sciences, 2014)
The Asmari Formation (Oligocene-Miocene), a thick carbonate succession of shallow- water carbonates of the intrashelf basin deposits of Zagros Mountains, has been studied to determine its microfacies and paleoenvironments. In the study area (Bandar-pol anticline), the Asmari Formation is subdivided into nine microfacies that are distinguished by petrographic analysis on the basis of their depositional textures and fauna. Consequently, five major depositional environments were identified in the formation. Based on the paleoecology and lithology, five distinct depositional settings can be recognized: tidal flat (MF1), lagoon (MF2-3- 4), shoal (MF5), restricted (MF6) and open marine (MF7-8-9). Based on the environmental interpretations, a ramp consisting of inner and middle parts prevails.
Keywords: Asmari Formation Bndarpol anticline Microfacies Carbonate ramp